2014
DOI: 10.1139/cjb-2013-0224
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth dynamics and root morphology of little-known species of Chenopodium from contrasted Andean habitats

Abstract: Plant morphology determines the access to soil resources, a feature crucial for early growth in annual species. Plant growth and root traits in little-known species of Andean chenopods were compared with the hypothesis that plants from low-resource habitats show traits that enhance resource capture. Three cultivated Chenopodium populations (two populations of the tetraploid Chenopodium quinoa Willd., one population of the diploid Chenopodium pallidicaule Aellen) and one population of their wild tetraploid rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
2
5
1
Order By: Relevance
“…Each of these clusters includes genetic materials from different origins, so no geographic pattern in tolerance was detected, a contrast with assertions by Alvarez‐Flores et al. (2014).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Each of these clusters includes genetic materials from different origins, so no geographic pattern in tolerance was detected, a contrast with assertions by Alvarez‐Flores et al. (2014).…”
Section: Discussioncontrasting
confidence: 66%
“…Alvarez‐Flores et al. (2014) also found that quinoa genotypes from dry‐habitat showed longer, coarser and more numerous root segments than wet‐habitat genotypes. Gámez et al (2019) proposed that greater root development and a better stomatal opening adjustment could help maintain seed yield of Rainbow quinoa under drought stress.…”
Section: Discussionmentioning
confidence: 92%
“…hircinum, while C. pallidicaule remained limited to the first 40 cm soil layer (Alvarez-Flores et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Finally, root system architecture and its relationship to soil moisture conditions has been studied in quinoa and quinoa relatives. Quinoa roots exhibit faster elongation and abundant and longer external branching of the roots that improve their foraging capacity compared to quinoa relatives C. hiricinum and C. pallidicaule [67,68]. Recently, a root system architecture and dynamics study was conducted in drought conditions, comparing C. hiricinum and C. pallidicaule , a rainy-habitat and a dry-habitat quinoa genotype, respectively.…”
Section: Droughtmentioning
confidence: 99%